Shock of Monetary Policy Transmission and Macroeconomic Variable in Indonesia: A Structural VAR Approach - Rizal Rahman H. Teapon; Rachman Dano Mustafa (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2018)
Abstract: Shock of Monetary Policy Transmission and Macroeconomic Variable in Indonesia: A Structural VAR Approach. The purpose of this paper is to find out how much the shock of monetary policy transmission affects macroeconomic variables in Indonesia and vice versa by using Structural Vector Autoregression (SVAR) model. The results showed that the transmission of monetary policy in Indonesia only gives a weak influence toward inflation, but it greatly stimulates economic growth. However, the shock of macroeconomic variables influences the transmission of monetary policy in Indonesia significantly. Keywords: Structural Vector Autoregression (SVAR), monetary policy, macroeconomic policy.Abstrak: Kejutan Transmisi Kebijakan Moneter dan Variabel Makro Ekonomi di Indonesia: Suatu Pendekatan Structural Vector Autoregression. Tujuan dari tulisan ini adalah untuk mengetahui berapa besar guncangan transmisi kebijakan moneter mempengaruhi variabel makro ekonomi di Indonesia dan sebaliknya, dengan menggunakan model Structural Vector Autoregression (SVAR). Hasil penelitian menunjukan bahwa transmisi kebijakan moneter di Indonesia masih lemah dalam mempengaruhi inflasi tetapi sangat kuat dalam merangsang pertumbuhan ekonomi. Sebaliknya, guncangan variabel makro ekonomi sangat signifikan dalam mempengaruhi transmisi kebijakan moneter di Indonesia. Kata kunci: Structural Vector Autoregression (SVAR), kebijakan moneter, kebijakan makro ekonomi